(untitled) (Research, Society and Development, 2023)
The article discusses cranio-cervical joints, specifically the atlanto-occipital and atlantoaxial joints. The atlanto-occipital joints include the occipital condyle and the superior articular surfaces of the first cervical vertebra (C1 or Atlas), allowing flexion, extension and lateral tilt of the head. The atlantoaxial joints include C1 and C2 (Axis) vertebrae, enabling rotation. Atlanto-occipital fusion is a rare congenital condition in which C1 fuses with the occipital bone of the skull. This can lead to narrowing of the Foramen Magnum, with or without compression of central structures (spinal cord or brain stem). Although this condition can be asymptomatic, when associated with other cranio-cervical anomalies, such as Basilar Invagination and Platybasia, it can bring instability to the neck, in addition to tonsillar herniation, neural compression and cerebral ischemia. This condition is related to an embryonic malformation of the Pro Atlas, which can occur in different regions of the joint. Furthermore, the type of fusion can vary, eventually resulting in stress at the C1-C2 junction, leading to subluxations and neurovascular complications. Despite its rarity, preoperative diagnosis using computed tomography or magnetic resonance imaging is essential to identify these changes and avoid injuries during surgery. In conclusion, atlanto-occipital fusion is a rare condition that, when associated with other anomalies, can cause damage to the central nervous system, highlighting the importance of adequate diagnosis and treatment. The objective of the study is to illustrate, discuss and investigate the prevalence of atlanto-occipital fusion in human skulls, which the authors found one case among the 117 skulls analyzed.